The influence of nutrition on HPV-associated inflammation: a systematic review and meta-analysis - Li, Yuan; Zhu, Lijuan (Frontiers in Nutrition, 2025)
BackgroundChronic infection with human papillomavirus (HPV) is a key etiologic cause of cervical intraepithelial neoplasia (CIN) and cervical cancer.MethodologyBy applying MeSH terms and keywords relating to HPV, nutrition, and inflammation, sources such as PubMed, EMBASE, the Cochrane Library, and Google Scholar were examined until April 2025. Two reviewers separately selected the studies, extracted the information, and assessed the possibility of bias. Pooled estimates were computed using random-effects, with GRADE assessing confidence. 77 studies from 17 countries were included, of which the most represented were the USA (16 studies), China (12), and Iran (6). The types of studies comprised 38 case–control, 11 cross-sectional, 7 randomized controlled trials (RCTs), 7 cohort studies, and 14 nested studies. Nutrients assessed included vitamins A, C, D, E, K, B-complex (particularly B6, B12, and folate), carotenoids (β-carotene, lycopene, lutein), and minerals like selenium, zinc, and calcium.ResultsThe higher dietary intake or serum levels of micronutrients were associated with reduced persistence of HPV and decrease the risk of CIN and cervical cancer. Key findings by subgroup include: Based on 8 studies, involving 2,003 women, a protective vitamin E (particularly α-tocopherol) effect against HPV and cervical neoplasia (SMD = 0.46 [0.36, 0.57]; p < 0.0001; I2 = 21.3%; GRADE: Moderate) was noted. Across 5 studies, including 727 women, both oral and vaginal vitamin D supplementation reduced CIN2/3 lesions and improved inflammatory markers (SMD = 0.81 [0.69, 0.93]; p < 0.00001; I2 = 0%; GRADE: High). From 6 studies (1,246 individuals) the consistent inverse associations between vitamin A intake/status and risk of cervical cancer (SMD = 0.77 [0.68, 0.87]; p < 0.0001; I2 = 16.6%; GRADE: Moderate) was observed. Across 4 studies (1,130 women), folate and Vitamin B12 showed protective role in reducing HPV persistence and CIN progression, with favorable effects on DNA methylation and viral clearance (SMD = 0.80 [0.65, 0.95]; p < 0.00001; I2 = 0%; GRADE: High). Selenium supplementation, notably in Iranian trials (GRADE: Moderate) improved oxidative and immune profiles and was associated with CIN2 regression. Zinc and calcium were associated with immune enhancement and viral suppression (GRADE: Low to moderate).